Correction and addendum to “The solution on the geography-problem of non-formal (almost) contact manifolds” [Topol. Appl. 317 (2022) 108186](S0166864122001882)(10.1016/j.topol.2022.108186) - Bock, Christoph (Topology and its Applications, 2024)
Proposition 2.1 and Theorem 2.2 in Topology Appl. 317 (2022), Article 108186, can easily be generalised: Any odd-dimensional solvmanifold is contact.
CRIS-Team Scopus Importer:2025-02-04

On rational homotopy and minimal models - Bock, Christoph (Forum Mathematicum, 2020)
We prove a result that enables us to calculate the rational homotopy of a wide class of spaces by the theory of minimal models.
CRIS-Team Scopus Importer:2020-11-27
Keywords: nilpotent spaces; Rational homotopy

The solution on the geography-problem of non-formal compact (almost) contact manifolds - Bock, Christoph (Topology and its Applications, 2022)
Let (m,b) be a pair of natural numbers. For m odd with m≥7 (resp. m≥5) and b=0 (resp. b=1) we show that there is a non-formal compact (almost) contact m-manifold with first Betti number b1=b. Moreover, in the case b=0 with m≥7, the manifold even is simply-connected.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Contact manifolds; Formality; Massey products